HISTORICAL-PHILOSOPHICAL AND PEDAGOGICAL - VALEOLOGICAL FOUNDATIONS OF HUMAN HEAITH PROTECTION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article examines the historical heritage of healthy lifestyle formation and the principles of modern pedagogical valeology. The study analyzes the ancient philosophy of the East and West, Islamic culture, and the contemporary experiences of countries such as Japan and China in promoting public health. It scientifically substantiates the role of pedagogical valeology in developing health preservation skills from childhood, the significance of physical activity in reducing mortality risks, and its place within the social policy of the state.